Penilaian E-Servqual Terhadap Fasilitas E-Learning dengan Menggunakan Analisa Faktor - Kristophorus Hadiono; Novita Mariana; Rina Candra Noor Santi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
The Covid-19 pandemic that has occurred to date has made learning activities that are usually carried out face-to-face, switch to networks by utilizing e-learning media. The transfer of learning activities to e-learning media has advantages and disadvantages so that it needs to be evaluated. This evaluation is carried out to see to what extent the service quality of e-learning media is used in learning activities. One way to assess service quality is using the e-service quality method. The purpose of this study was to determine the quality of e-learning services. The service quality assessment factors used in this study are tangibility, reliability, responsiveness, assurance, and empathy. The research method used in this research is quantitative method and the data collection period starts from August 2020 to February 2021. 174 students was participated in this study, with the largest proportion being semester 7 students. The instrument used has good validity with a KMO value of more than 0, 5 and is reliable with a Cronbach's alpha value of more than 0.6. The final results of the study can be concluded that five factors measuring the quality of electronic services can be used to measure the quality of electronic learning services and the most influential factor is the assurance factor.